Why Psychology Matter in Public Sector Budgeting ? An Indonesia Research Evidence - Yuhertiana, Indrawati (International Journal of Psychosocial Rehabilitation, 2020)
This is a critical opinion to explain why public sector need to notify psychology in the budgeting process. This article convinced that psychology studies important to understand people involved in budgeting process, in all of budget cycle, from preparation step, ratification, implementation and the accountability of budget process. Archival research used to dig depth understanding behavior in four budget cycle. The data observed in research paper that was presented in Indonesia accounting symposium for 18 years. It was found that the role of psychology as personal problem increased related the impact of public sector reform. Pressure to change a new accounting standard, accounting techniques required a new mind setting up about the value of new public management i.e accountability and transparency. This research has implication in public sector path in using behavioral focus or variable instead of the technical aspect of public sector budgeting. In practical, by understanding the behavioral aspect especially psychology of budgeting actors, it makes easier for government or parliament to make decision related controlling the behavior aspect